Experiences of women recently diagnosed with HIV - Jurie, Khuselwa (Rhodes University, Faculty of Humanities, Department of Psychology, 2015)
The focus of this study is on the experiences of a small sample of local women who have been recently diagnosed with HIV. The aim of the research was to give these women an opportunity to express their first-hand, personal accounts of living with HIV. Five isiXhosa-speaking women were recruited and interviewed. These accounts were collected and analysed within in the methodological framework of Interpretative Phenomenological Analysis, a qualitative approach that is becoming increasingly popular in the broad fields of health and clinical psychology. Data was analysed for meaningful units, which were interpreted inductively and hermeneutically, and categorised into super-ordinate themes. Five themes within the participants' experiences of living with HIV were identified: (1) experiences of diagnosis, (2) experiences of stigma, (3) social support, (4) coping strategies, and (5) HIV as one of many assaults to self. Implicated in these experiences are the ways in which these women have appraised themselves and their situation after an HIV-positive diagnosis, appraisals that are shaped by HIV-related stigma. A variety of negative emotional reactions are common following the diagnosis, often compounded by the direct experiences of HIV-related stigma. Women in the study adopted different kinds of coping strategies based on the resources and social support available to them. Also significant is that for these women who had typically endured a variety of traumatic life events, a positive diagnosis was simply one of many life challenges
Keywords: HIV-positive women -- South Africa -- Eastern Cape; Stigma (Social psychology); HIV (Viruses) -- Diagnosis; AIDS (Disease) in women -- Social aspects -- South Africa -- Eastern Cape